An Analysis of Renewable Energy Potential and Deployment towards Bali Net-Zero Emission - Widianto, I. G. A.; Sukerayasa, I W.; Setiawan, I N.; Giriantari, I. A. D.; Ariastina, W. G.; Santiari, D. A. S.; Kumara, I N. S. (Institute for Research and Community Services Udayana University, 2025)
The Bali Provincial Government has declared a commitment to achieve Net Zero Emissions (NZE) by 2045. This involves transitioning from non-renewable energy sources to renewable energy to reduce emissions from the energy sector. The policy aligns with the growing demand for electricity and the abundant renewable energy potential in Bali Island. Three scenarios were simulated using the Open Source energy Modelling System (OSeMOSYS) software to evaluate Bali power system with renewable energy potential from 2024 to 2045. The results indicated that to achieve NZE in year 2045, for the optimistic scenario, the renewable energy share may reach 85.62% and result in a reduced emission to 5.78 million tons of CO2eq. For the moderate scenario, Bali Island is required to have a renewable energy share of about 84.13% and 4.15 million tons of CO2eq at the end of year 2045. Meanwhile, for the pessimistic scenario, the renewable energy share must be about 82.65% and with an emission of 3.19 million tons of CO2eq in 2045.